Electrochemistry of Nitrated N‐Confused Free‐Base Tetraaryl‐Porphyrins in Nonaqueous Media. Issue 41 (26th August 2015) - Ye, Lina; Ou, Zhongping; Fang, Yuanyuan; Xue, Songlin; Chen, Xueyan; Lu, Guifen; Jiang, Xiaoqin; Kadish, Karl M.
Abstract Four nitrated N‐confused free‐base tetraarylporphyrins were synthesized and characterized by electrochemistry and spectroelectrochemistry in nonaqueous media. The examined compounds are represented as NO2(Ar)4NcpH2, where NO2(Ar)4Ncp is the dianion of a tetraaryl N‐confused porphyrin with an inner carbon bound NO2 group and Ar is a p‐CH3OPh, p‐CH3Ph, Ph or p‐ClPh substituent on each meso‐position of the macrocycle. UV/Vis spectra and NMR spectroscopy data indicate that the same form of the porphyrin exists in CH2Cl2 and DMF which is unlike the case of non‐NO2 N‐confused porphyrins. The Soret band of NO2(Ar)4NcpH2 exhibits a 30–36 nm red‐shift in CH2Cl2 and DMF as compared to the spectrum of the non‐NO2 N‐confused porphyrins. The first two reductions and first oxidation of NO2(Ar)4NcpH2 are reversible in CH2Cl2 containing 0.1 M TBAP. The measured HOMO–LUMO gap averages 1.65 V in CH2Cl2 and 1.53 V in DMF, with both values being similar to those of the non‐NO2 substituted compounds. The nitro group on the inverted pyrrole is itself not reduced within the negative potential limit of CH2Cl2 or DMF, but its presence significantly affects both the UV/Vis spectra and redox potentials.